Tingkat Pengetahuan Talasemia Pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung - Intan Purnamasari; Yani Triyani; Sara Puspita (Jurnal Riset Kedokteran, 2024)
Abstract. Thalassemia is a congenital blood disorder caused by failure to form hemoglobin which damages red blood cells and results in anemia or lack of blood in sufferers. As the number of thalassemia sufferers increases, awareness of the importance of knowledge of thalassemia must be raised among the public, especially among students at the Faculty of Medicine, Bandung Islamic University as medical personnel in the future must be able to educate the public well. This research aims to determine the level of knowledge of students at the Faculty of Medicine, Islamic University of Bandung about thalassemia. The research subjects were 204 people. This research uses an analytical observational method with a cross-sectional approach. The results of this research show that the majority of students at the Faculty of Medicine, Bandung Islamic University for the 2022/2023 academic year have a good level of knowledge regarding thalassemia (85.3%). A good level of knowledge among students, especially students at the Faculty of Medicine, Bandung Islamic University, is influenced by several things. Students can get information from various sources, starting from formal education and information available on social media. The sources of information obtained by students can increase understanding and knowledge regarding the definition, diagnosis, management and prevention of thalassemia. Abstrak. Talasemia adalah kelainan darah bawaan yang disebabkan oleh kegagalan pembentukan hemoglobin yang merusak sel darah merah dan mengakibatkan anemia atau kekurangan darah pada penderita. Seiring bertambahnya jumlah penderita talasemia, kesadaran akan pentingnya pengetahuan talasemia harus ditumbuhkan di kalangan masyarakat khususnya pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung sebagai tenaga medis di masa yang akan datang sehingga harus mampu mengedukasi masyarakat dengan baik. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan mahasiswa Fakultas Kedokteran Universitas Islam Bandung tentang talasemi. Subjek penelitian sebanyak 204 responden. Penelitian ini menggunakan metode observasional analitik dengan pendekatan potong lintang. Hasil penelitian ini menunjukkan bahwa hasil dari penelitian ini menunjukan bahwa sebagian besar Mahasiswa Fakultas Kedokteran Universitas Islam Bandung tahun akademik 2022/2023 memiliki tingkat pengetahuan yang baik mengenai talasemia (85.3%). Tingkat pengetahuan yang baik pada mahasiswa khususnya pada mahasiswa Fakultas kedokteran Universitas Islam Bandung dipengaruhi oleh beberapa hal. Mahasiswa dapat mendapatkan informasi dari berbagai sumber, mulai dari pendidikan formal maupun informasi yang tersedia di media sosial. Sumber informasi yang didapat oleh mahasiswa dapat meningkatkan pemahaman serta pengetahuan terhadapa pengertian, diagnosis, tatalaksana, serta pencegahan talasemia.